The Influence of Parenting Styles and Academic Self Efficacy on Mathematics Learning Achievement of Elementary Students - Lestrari, Heming; Murwaningsih, Tri; Supianto, Supianto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This research aims to 1) determine the influence of parenting styles on Mathematics learning achievement; 2) determine the influence of academic self-efficacy on learning achievement in Mathematics; and 3) determine the influence of parenting styles and self-efficacy on learning achievement in Mathematics. This research uses a quantitative approach. The research subjects were students in grades 4, 5, and 6 of elementary schools. The data collection techniques used were questionnaires and documentation. Data analysis was carried out using simple and multiple linear regression formulas. The results of the research show that 1) There is a positive and significant influence between parental parenting styles on student learning achievement in Mathematics; 2) There is a positive and significant influence between self-efficacy on student learning achievement in Mathematics; and 3) There is a positive and significant influence between parenting styles and self-efficacy on student learning achievement in Mathematics. Based on the results of research, it can be stated that to optimize communication between the school and parents, so that in the future the school can improve and optimize student learning achievement by discussing with parents so that positive interactions occur in the school environment, outside the school and family